Using Whatsapp Group as a Means to Improve Non-English College Major Students' Motivation to Speak English - Fatimah, Siti; Rahima, Annisa Rizqa; Basuki, Hendra; Safitri, Khulia; Rahman, M Arinal; Nor Azhar, Nurul Fathihah; Handrianto, Ciptro (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This study deals with how students' perspectives on using WhatsApp groups improve students' speaking ability. Motivation is the strength students have inside or outside of themselves that encourages them to achieve something. The sample of this study is students taken from UPB class of Antasari State Islamic University. In collecting the data, this study used questionnaires for the respondents. Close-ended questionnaires and open-ended questionnaires will be used to get data on the use of the WhatsApp group in improving students' speaking ability. The researchers employed the Likert scale to get the information related to two indicators in this research. 5 was given for strongly agree (SA), 4 for agree (A), 3 for neutral (N), 2 for disagree (D), and 1 for strongly disagree (SD). Meanwhile, the open-ended questionnaire consisted of 8 questions that asked about the role of the WhatsApp group in learning to speak. The results of the study showed that learning using WhatsApp group as a means of speaking can improve students' motivation in learning English and produce positive effects and benefits for non-English college major students in improving their speaking skills.